PENGARUH PENGGUNAAN BLOWER ELEKTRIK TERHADAP PERFORMA MESIN SEPEDA MOTOR SISTEM INJEKSI - Suwahyo, Suwahyo; Septiyanto, Angga; Manfa'at, Manfa'at (Sainteknol : Jurnal Sains dan Teknologi, 2017)
The age of motorcycle usage impacts on decreasing engine performance, the longer the motorcycle is used it will decrease its performance. There are several things that can be done to keep the engine performance in good running condition, one of them is by increasing the amount of air entering the cylinder using an electric blower. This study aims to determine the magnitude of the effect of electric blowers on the power, torque, and fuel consumption of motorcycle injection system. This research uses experimental method by setting electric blower on motorcycle injection system, then testing the engine performance with the handling when the blower off and when the blower on. The research data is obtained by testing the research objects which include power, torque, and fuel consumption that is pertamax fuel and variation of incoming air volume using blower output regulating valves 300, 600, and 900. The result shows that there is an influence of electric blowers on motorcycle injection system in increasing engine performance. The increase of power and torque is caused by the increased mass of air and fuel coming into the cylinder impacting on increasing the calorific value. The power increases by 0.49 kW or 9.42%. The torque increases by 1.41 Nm or 5.87%. The fuel consumption increases by 0.23 kg / h or 41.14%.